Web designear: bases conceituais e método de projetação para interfaces web - Lima, Jefferson Silva (2014)
This work was motivated by my interest in combining issues concerning planning principles applied to graphic - visual products (printed) and, especially , the chart - virtual products (Internet). The main issue was to start by understanding the projective bases of these media , the world of virtual sites or web sites . Faced with so many projective factors ( eg . , Aesthetic, ergonomic, technological ) to be considered in a good graphic - virtual product , certainly , it appears that some methodological knowledge is needed to be set up so much information on a single type product service . For this it was necessary to use a qualitative research approach with in- Tuito to describe, understand and explain the phenomena involved in such design practice , in order to produce sufficient and necessary to the foundation of the work knowledge, which was directed by descriptive and exploratory research , supported mainly by the use of literature and the field study , which respectively aim to recog - lher information or prior knowledge about the problem and understand the prag - matic form the object of study from the viewpoint the observer . This research sought to show that even with so many books already released on " interface design for the web" , the apparent ease with which you can design a product to WWW allows few understand web design as one of the specialties of Design, whose practice project , however, is essentially founded on the teachings of industrial Design . In short , this work is intended for all those who need to create graphical interfaces for web and not having a more intimate relationship with the design , they are advertising , computer engineers , design students at the academy freshmen , self-taught , etc. . whose premise rests on knowing and understanding the conceptual basis of the design of interfaces for web , whose practice is primarily founded on the teachings of Industrial Design.